Full Factorial Microfluidic Designs and Devices for Parallelizing Human Pluripotent Stem Cell Differentiation. (February 2019) - Chadly, Duncan M.; Oleksijew, Andrew M.; Coots, Kyle S.; Fernandez, Jose J.; Kobayashi, Shun; Kessler, John A.; Matsuoka, Akihiro J.
Human pluripotent stem cells (hPSCs) are promising therapeutic tools for regenerative therapies and disease modeling. Differentiation of cultured hPSCs is influenced by both exogenous factors added to the cultures and endogenously secreted molecules. Optimization of protocols for the differentiation of hPSCs into different cell types is difficult because of the many variables that can influence cell fate. We present microfluidic devices designed to perform three- and four-factor, two-level full factorial experiments in parallel for investigating and directly optimizing hPSC differentiation. These devices feature diffusion-isolated, independent culture wells that allow for control of both exogenous and endogenous cellular signals and that allow for immunocytochemistry (ICC) and confocal microscopy in situ. These devices are fabricated by soft lithography in conjunction with 3D-printed molds and are operable with a single syringe pump, eliminating the need for specialized equipment or cleanroom facilities. Their utility was demonstrated by on-chip differentiation of hPSCs into the auditory neuron lineage. More broadly, these devices enable multiplexing for experimentation with any adherent cell type or even multiple cell types, allowing efficient investigation of the effects of medium conditions, pharmaceuticals, or other soluble reagents.